Theoretical Investigations on the Mechanical, Magneto-Electronic Properties and Half-Metallic Characteristics of ZrRhTiZ (Z = Al, Ga) Quaternary Heusler Compounds - Wenbin Liu; Xiaoming Zhang; Hongying Jia; Rabah Khenata; Xuefang Dai; Guodong Liu (Applied Sciences, 2019)
The electronic, magnetic, and mechanical properties were investigated for ZrRhTiZ (Z = Al, Ga) quaternary Heusler compounds by employing first-principles calculations framed fundamentally within density functional theory (DFT). The obtained electronic structures revealed that both compounds have half-metallic characteristics by showing 100% spin polarization near the Fermi level. The half-metallicity is robust to the tetragonal distortion and uniform strain of the lattice. The total magnetic moment is 2 μB per formula unit and obeys the Slater-Pauling rule, Mt = Zt − 18 (Mt and Zt represent for the total magnetic moment and the number of total valence electrons in per unit cell, respectively). The elastic constants, formation energy, and cohesive energy were also theoretically calculated to help understand the possibility of experimental synthesis and the mechanical properties of these two compounds.